Poly[[{μ2-5-[(dimethylamino)(thioxo)methoxy]benzene-1,3-dicarboxylato-κ4O1,O1′:O3,O3′}(μ2-4,4′-dipyridylamine-κ2N4:N4′)cobalt(II)] dimethylformamide hemisolvate monohydrate] - Hui-Yu Qin; Bing-Guang Zhang; Qiao-Zhen Sun (IUCrData, 2024)
In the crystal structure of the title compound, {[Co(C11H9NSO5)(C10H9N3)]0.5C3H7NO·H2O}n or {[Co(dmtb)(dpa)]·0.5DMF·H2O}n (dmtb2– = 5-[(dimethylamino)thioxomethoxy]-1,3-benzenedicarboxylate and dpa = 4,4′-dipyridylamine), an assembly of periodic [Co(C11H9NSO5)(C10H9N3)]n layers extending parallel to the bc plane is present. Each layer is constituted by distorted [CoO4N2] octahedra, which are connected through the μ2-coordination modes of both dmtb2– and dpa ligands. Occupationally disordered water and dimethylformamide (DMF) solvent molecules are located in the voids of the network to which they are connected through hydrogen-bonding interactions.